Compressibility Studies of Solvation Behaviour of Lithium and Sodium Ions in Nitromethane + Dimethylsulfoxide Binary Mixtures at 298.15 K - Anand, Hardeep; Singh, Narender; Kumar, Suresh; Rani, Manju (Asian Journal of Chemistry, 2021)
The isentropic compressibilities (Ks) and apparent molal isentropic compressibilities (Ks,f) of lithium perchlorate (LiClO4), sodium perchlorate (NaClO4), sodium tetraphenylborate (NaBPh4), tetrabutylammonium tetraphenylborate (Bu4NBPh4) and tetrabutylammonium perchlorate (Bu4NClO4), have been calculated from measured ultrasonic velocity (u) and density (ρ) of these salts in the concentration range 0.001 to 0.60 mol Kg-1 in the mixed binary solutions of nitromethane (NM) and dimethyl sulfoxide (DMSO) containing 0, 20, 40, 60, 80 and 100 mol% of DMSO in NM at 298.15 K. Limiting values of apparent molal isentropic compressibilities (K°s,f) for various salts were evaluated and split into the contributions (K°s,f)± of the individual ions. Exceptionally large and negative (K°s,f)± values were obtained whose variation with solvent composition shows strong solvation of both Li+ and Na+ in NM + DMSO mixtures at all compositions of the mixed binary solutions. Solvation of Li+ and Na+ increases as mol% of DMSO in NM increases. Solvation exhibited by Li+, however, is much stronger than Na+ in all compositions of the mixtures. Solvation exhibited by ClO4– in NM + DMSO mixtures is weak which perchlorate ion shows by having some interactions with DMSO in the DMSO-rich compositions of the mixtures. The large and positive values for Bu4N+ and Ph4B– are indicative of some special type of interactions, mainly solvophobic with the solvent molecules.